Análise do autoconceito e autocontrole de crianças negras a partir da identidade social - Almeida, Saulo Santos Menezes de (2012)
Prejudice, albeit subtle, is still present in society and this has also affected blacks in a society that no longer wants to prove as hostile, bus still subtle prejudice rooted in the discourses and attitudes. Racial prejudice is therefore a construction of derogatory and hostile attitudes against socially marginalized groups, knowing that the term racial group is defined by social attitudes, not only biology or appearance. In this sense, this research seeks to question how the children, who are also participating in a social environment, respond to these issues of prejudice and identity processes, and to what extent self-control and sel-concept of these children are affected. The Self is a product of interaction between the person and their environment during their process of social construction, and Self-control is a way of controlling their own behavior, often in conflict situations, in accordance with standards set by society. Thus, analyzed 100 children from two public schools in the interior of Sergipe, aged between 11 and 12 years, 47 boys and 53 girls. The instruments used in understanding the questionnaire were bioecological investigation of racism and scales assessing self-concept and self-control. The results showed that children seek a greater identification with the category of color "white", valuing the stereotypes from this pattern, and self-concept and self-proved at low levels. Thus, it is thinking of bleaching processes in an attempt to value themselves and the group using an approximation of the group more valued socially.